Extramedullary Hematopoiesis in a Man With β-Thalassemia: An Uncommon Cause of an Adrenal Mass - Shahryar Zeighami (Shiraz University of Medical Sciences, 2015)
Introduction Extramedullary hematopoiesis (EMH) commonly occurs in the spleen, liver and lymph nodes. Rare cases of EMH in the adrenal gland have been reported. Case Presentation We report the case of a 33-year-old man from the South of Iran suffering from major β-thalassemia, who underwent open left adrenalectomy and the histopathology revealed EMH. Conclusions In patients in which a history of hematologic disorders exists, careful imaging and hormonal assay should be done to certify a diagnosis of EMH. However, the surgical management becomes inevitable in certain cases.